Diversity of Pathogenic Fungi on Maize Seeds (Zea mays L.) in Traditional Markets of Kedaton District, Bandar Lampung - Hernawan, Renaldy; Yulianty, Yulianty; Azizah, Enur; Irawan, Bambang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Corn (Zea mays L.) is an important food commodity widely consumed and sold in traditional markets. However, poor post-harvest handling and storage conditions make corn kernels susceptible to infections by pathogenic fungi, which can reduce quality and potentially produce harmful mycotoxins. This study aimed to determine the diversity and dominant genera of pathogenic fungi infecting corn sold in traditional markets in Kedaton District, Bandar Lampung. The research was conducted from June to July 2025 using a purposive sampling method across seven traditional markets, with a total of 21 samples. Fungal isolation was carried out on PDA media, followed by macroscopic and microscopic identification. The results showed that four fungal genera infected the corn kernels, namely Fusarium sp., Rhizopus sp., Penicillium sp., and Aspergillus sp. Fusarium sp. was identified as the most dominant genus, found in 12 out of 21 samples, while Aspergillus sp. had the lowest occurrence, appearing in only one sample. The presence of these fungi indicates that corn storage practices in traditional markets are still inadequate and may pose health risks. Further studies at the molecular level and tests of natural antifungal extracts are recommended to strengthen fungal identification and improve post-harvest fungal control efforts.